2023
DOI: 10.3389/frvir.2023.1177855
|View full text |Cite
|
Sign up to set email alerts
|

Different realities: a comparison of augmented and virtual reality for the sensemaking process

Lee Lisle,
Kylie Davidson,
Edward J. K. Gitre
et al.

Abstract: Analysts perform sensemaking on large complex multimedia datasets in order to extract concepts, themes, and other kinds of insights from them. Immersive analytics, in particular, puts users in virtual environments that allow them to explore data in a unique way where they can interact and move through the data. Previous research using virtual reality immersive analytics tools found users wanting to refer to real-world objects or understand the physical world around them while continuing to perform their analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…AVR is proposed as an interactive approach, that aims to amplify the effects of motor training, both directly and indirectly, increasing the patient’s motivation and satisfaction, promoting greater adherence and participation to treatment, and training also cognitive aspects of fall risk ( 14 ). For these reasons, AVR is considered an emerging and promising therapeutic tool in neurorehabilitation ( 15 ). In this regard, positive results emerged from the clinical trial of Gulcan et al ( 16 ) in which AVR-VR TT has been demonstrated to be effective in PD on most of spatial–temporal gait parameters compared to conventional physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…AVR is proposed as an interactive approach, that aims to amplify the effects of motor training, both directly and indirectly, increasing the patient’s motivation and satisfaction, promoting greater adherence and participation to treatment, and training also cognitive aspects of fall risk ( 14 ). For these reasons, AVR is considered an emerging and promising therapeutic tool in neurorehabilitation ( 15 ). In this regard, positive results emerged from the clinical trial of Gulcan et al ( 16 ) in which AVR-VR TT has been demonstrated to be effective in PD on most of spatial–temporal gait parameters compared to conventional physical therapy.…”
Section: Introductionmentioning
confidence: 99%